Effects of limestone solubility on the efficacy of a novel consensus bacterial 6-phytase variant to improve mineral digestibility, retention, and bone ash in young broilers fed low-calcium diets containing no added inorganic phosphate. (14th October 2022) - Bello, Abiodun; Kwakernaak, Cees; Dersjant-Li, Yueming
Abstract: This study evaluated the effect of limestone solubility on the capacity of a novel consensus bacterial 6-phytase variant (PhyG ) to improve phosphorus (P) and calcium (Ca) digestibility, retention, and utilization in low-Ca broiler diets containing no added inorganic phosphate (Pi). Male Ross 308 broilers ( n = 1, 152) were fed one of 16 experimental diets from 11 to 21 d of age in a randomized complete design (12 birds/cage, 6 cages/treatment). Diets comprised three positive controls (PC3, PC2, and PC1) containing 1.8, 1.2, or 0.6 g/kg MCP-P and 7.7, 7.0, or 6.2 g/kg Ca, respectively, and a negative control (NC ) containing no added Pi (4.4 g/kg P; 2.8 g/kg phytate-P) and 5.5 g/kg Ca from either low or high solubility limestone (LSL or HSL, respectively, [with 42% and 97% solubility after 5 min at pH 3.0]), supplemented with 0, 250, 500, 1, 000, or 2, 000 FTU/kg of PhyG. Fecal samples collected on days 18 to 20 and ileal digesta collected on day 21 were analyzed for titanium dioxide, Ca, P, and phytate (IP6, inositol hexakisphosphate). Tibias (day 21) were analyzed for ash content. Data were analyzed by factorial analysis (2 limestone solubilities × 4 MCP-P levels and 2 limestone solubilities × 5 phytase dose levels) and exponential regression. Increasing dose levels of PhyG resulted in an exponential increase ( P < 0.01) in the apparent ileal digestibility (AID ) of P, ileal digestible P content of the diet, ileal IP6 content, and IP6 disappearance in birds fed either HSL or LSL diets, but AID Ca and ileal digestible Ca were exponentially increased by the phytase only in HSL diets ( P < 0.01). Relative to HSL, the LSL increased AID P, ileal digestible P, and IP6 disappearance ( P < 0.05) but reduced AID Ca, ileal digestible Ca, and retainable Ca ( P < 0.05), resulting in reduced retainable P and tibia ash. Phytase exponentially increased the apparent total tract digestibility of P, retainable P, and tibia ash in HSL and LSL diets, but at or above 500 FTU/kg values were higher in HSL than LSL (interaction P < 0.05). The findings highlight that phytase dose–response effects on mineral digestibility and utilization are different for high- and low-solubility limestones, and it is therefore recommended to use digestible rather than total Ca content during diet formulation to ensure an optimal balance of Ca and P, especially in low-Ca diets. In diets containing HSL, higher phytase dose levels may be needed to compensate for the low digestible P content of the basal diet. Abstract : A novel consensus bacterial 6-phytase variant is shown to be effective in improving mineral digestibility in phosphorus-deficient, low-calcium diets containing either high- or low-solubility limestone but was more effective in diets containing low-solubility limestone. A higher phytase dose level may be required to meet phosphorus requirements in diets containing high solubility limestone to compensate for their low digestible phosphorus content. Lay Summary: In broilers, an excess of dietary calcium (Ca) or imbalance with phosphorus (P) can impair mineral digestion and utilization. As a result, diets are being formulated with less Ca, but the quality of the added Ca (that is mainly from limestone) is also important. This study investigated effects of limestone solubility (high [HSL] vs. low [LSL]) on the capacity of a novel consensus bacterial 6-phytase variant, PhyG, to improve P and Ca digestion and utilization in low-Ca diets containing no added inorganic phosphate. Increasing the phytase dose increased ileal P and phytate digestibility and the digestible P content of the diet at 21 d of age regardless of limestone solubility and reduced the negative effects of HSL (relative to LSL). Total tract digestibility of P and Ca, retainable P and Ca, and tibia ash were also increased by phytase, but responses were reduced with LSL relative to HSL. The findings highlight that phytase dose-responses differ in diets containing different limestones and it is therefore recommended to formulate diets based on the content of digestible rather than total Ca to ensure that Ca requirements are met but not exceeded, with optimal phytase efficacy. In diets containing HSL, a higher PhyG dose level is needed to meet the requirement for P.